Novel screening method based on menadione mediated rapid reduction of tetrazolium salt for testing of anti-mycobacterial agents - Singh, Upasana; Akhtar, Shamim; Mishra, Abhishek; Sarkar, Dhiman (Journal of Microbiological Methods, 2011)
A microplate-based rapid, inexpensive and robust technique is developed by using tetrazolium salt 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) and menadione to determine the viability of Mycobacterium tuberculosis, Mycobacterium bovis BCG and Mycobacterium smegmatis bacilli in microplate format. In general, XTT reduction is an extremely slow process which takes almost 24 h to produce a detectable signal. Menadione could drastically induce this reduction to an almost equal extent within a few minutes in a dose dependent manner. The reduction of XTT is directly proportional to the cell concentration in the presence of menadione. The standardized protocol used 200 mu M of XTT and 60 mu M of menadione in 250 mu l of cell suspension grown either in aerobic or anaerobic conditions. The cell suspension of M. bovis BCG and M. tuberculosis were incubated for 40 min before reading the optical density at 470 nm whereas M. smegmatis was incubated for 20 min. Calculated Signal/Noise (S/N) ratios obtained by applying this protocol were 5.4, 6.4 and 9.4 using M. bovis BCG. M. tuberculosis and M. smegmatis respectively. The calculated Z' factors were > 0.8 for all mycobacterium bacilli indicating the robustness of the XTT Reduction Menadione Assay (XRMA) for rapid screening of inhibitors. The assay protocol was validated by applying 10 standard anti-tubercular agents on M. tuberculosis, M. bovis BCG and M. smegmatis. The Minimum Inhibitory Concentration (MIC) values were found to be similar to reported values from Colony Forming Unit (CFU) and REMA (resazurin microplate assay) assays. Altogether. XRMA is providing a novel anti-tubercular screening protocol which could be useful in high throughput screening programs against different physiological stages of the bacilli. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Menadione; Mycobacterium tuberculosis; Tetrazolium salt; XRMA

Nitrate reduction pathways in mycobacteria and their implications during latency - Khan, Arshad; Sarkar, Dhiman (Microbiology-SGM, 2012)
Mycobacterial persistence has gained a lot of attention with respect to developing novel antitubercular drugs, which could drastically reduce the duration of tuberculosis (TB) therapy. A better understanding of the physiology of Mycobacterium tuberculosis, and of the metabolic state of the bacillus during the latent period, is a primary need in finding drug targets against persistent TB. Recent biochemical and genetic studies of nitrate reduction in mycobacteria have revealed the roles of distinct proteins and enzymes involved in the pathway. The differential degree of nitrate reduction among pathogenic and non-pathogenic mycobacterial species, and its regulation during oxygen and nutrient limitation, suggest a link between nitrate reduction pathways and latency. The respiratory and assimilatory reduction of nitrate in mycobacteria may be interconnected to facilitate rapid adaptation to changing oxygen and/or nitrogen conditions, increasing metabolic flexibility for survival in the hostile host environment. This review summarizes the nitrate metabolic pathways operative in mycobacteria to provide an insight into the mechanisms that M. tuberculosis has evolved to adapt successfully to the host environment.

Nitrite reductase NirBD is induced and plays an important role during in vitro dormancy of mycobacterium tuberculosis - Akhtar, Shamim; Khan, Arshad; Sohaskey, Charles D.; Jagannath, Chinnaswamy; Sarkar, Dhiman (Journal of Bacteriology, 2013)
Mycobacterium tuberculosis is one of the strongest reducers of nitrate among all mycobacteria. Reduction of nitrate to nitrite, mediated by nitrate reductase (NarGHJI) of M. tuberculosis, is induced during the dormant stage, and the enzyme has a respiratory function in the absence of oxygen. Nitrite reductase (NirBD) is also functional during aerobic growth when nitrite is the sole nitrogen source. However, the role of NirBD-mediated nitrite reduction during the dormancy is not yet characterized. Here, we analyzed nitrite reduction during aerobic growth as well as in a hypoxic dormancy model of M. tuberculosis in vitro. When nitrite was used as the sole nitrogen source in the medium, the organism grew and the reduction of nitrite was evident in both hypoxic and aerobic cultures of M. tuberculosis. Remarkably, the hypoxic culture of M. tuberculosis, compared to the aerobic culture, showed 32- and 4-fold-increased expression of nitrite reductase (NirBD) at the transcription and protein levels, respectively. More importantly, a nirBD mutant of M. tuberculosis was unable to reduce nitrite and compared to the wild-type (WT) strain had a >2-log reduction in viability after 240 h in the Wayne model of hypoxic dormancy. Dependence of M. tuberculosis on nitrite reductase (NirBD) was also seen in a human macrophage-based dormancy model where the nirBD mutant was impaired for survival compared to the WT strain. Overall, the increased expression and essentiality of nitrite reductase in the in vitro dormancy models suggested that NirBD-mediated nitrite reduction could be critical during the persistent stage of M. tuberculosis.

New butenolide cinnamate and other biological active chemical constituents from Polygonum glabrum - Said, Madhukar S.; Chinchansure, Ashish A.; Nawale, Laxman; Durge, Ankita; Wadhwani, Ashish; Kulkarni, Smita S.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2015)
Phytochemical investigation of the methanol extract of the aerial parts of Polygonum glabrum afforded one new natural product (-)-2-methoxy-2-butenolide-3-cinnamate (1) along with six known compounds, -hydroxyfriedalanol (2), 3-hydroxy-5-methoxystilbene (3), (-) pinocembrin (4), sitosterol-(6-O-palmitoyl)-3-O–d-glucopyranoside (5), (-) pinocembrin-5-methyl ether (6) and sitosterol-3-O–d-glucopyranoside (7). Compound 1 showed promising in vitro anti-HIV-1 activity against primary isolates HIV-1(UG070) (X4, subtype D) and HIV-1(VB59) (R5, subtype C) assayed using TZM-bl cell line with IC50 in the range of 15.68-22.43g/mL. The extract showed TI in the range of 19.19-27.37 with IC50 in the range of 10.90-15.55g/mL. Compounds 1, 3 and 4 exhibited in vitro anti-mycobacterium activity against Mycobacterium tuberculosis H37Ra with IC50 values of 1.43, 3.33 and 1.11g/mL in dormant phase and 2.27, 3.33 and 1.21g/mL in active phase, respectively. Compound 4 was found to be the most active antiproliferative with IC50 values of 1.88-11.00g/mL against THP-1, A549, Panc-1, HeLa and MCF7 cell lines.
Keywords: anti-HIV-1; anti-mycobacterium; antiproliferative; phytochemicals; Polygonaceae; Polygonum glabrum

Naturally occurring anti-TB agents: isolation, chemical transformations and in vitro antitubercular activities of secondary metabolites of rhizomes of alpinia galanga - Valkute, Tushar R.; Arkile, Manisha A.; Sarkar, Dhiman; Bhattacharya, Asish K. (Planta Medica International Open, 2016)
A bioactivity-guided chemical examination of the acetone extract of the rhizomes of Alpinia galanga led to the isolation of six sec-ondary metabolites, eucalyptol derivative (1)andphenylpropa-noids (2–6). The structures of all of the isolated compounds (1–6)wereelucidatedonthebasisoftheirspectraldata.Theisolatedcompounds (1–6)werein vitro assayed against active and dor-mant phenotypes of Mycobacterium tuberculosis H37Ra, respec-tively. Interestingly, 1′S-1′-acetoxychavicol acetate (2)showedgood antitubercular activities against both active and dormantphenotypes of M. tuberculosis with IC50 values of 1.04 µM and2.69 µM, respectively. Tsuji-Trost and homodimerization reac-tions of the active compound (2)respectivelyresultedinthefor-mation of two analogues, 7and 8.Bothofthesesynthesizedana-logues were also found to be active in vitro against active [IC50 sof3.24 and 3.87 µM, respectively, for compounds 7and 8]anddor-mant [IC50 sof8.33and2.41µM,respectively,forcompounds7and 8]phenotypesofM. tuberculosis H37Ra, respectively.

New dinor-cis-labdane diterpene and flavonoids with antimycobacterium activity from colebrookea oppositifolia - Chinchansure, Ashish A.; Arkile, Manisha A.; Shinde, Dinesh R.; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2016)
The new 14,15-dinor-cis-labdane diterpene, named (+)-14,15-dinor-9α-hydroxy-cis-labd-11(E)-en-13-one (1), was isolated from the acetone extract of the aerial parts of Colebrookea oppositifolia, along with the known compounds alnustin (2), mosloflavone (3), flindulatin (4), 5,6,7-trimethoxy baicalein (5), tanetin (6), scutellarein 4′-methyl ether (7), apigenin (8), caffeic acid (9), anisofolin A (10), apigetrin (11), and forsythoside A (12). Structures of the new and known compounds were established by detailed analysis of 1D and 2D nuclear magnetic resonance studies. The isolated compounds 1–12 were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis in both dormant and active phases. Compounds 1, 7, and 8 exhibited inhibitory activity against M. tuberculosis with IC50 values in the range of 8.1–55.0 µM (MIC 14.4–119.7 µM) in the active phase and 7.4–43.5 µM (MIC 11.5–123.3 µM) in the dormant phase. Similarly 1, 7, and 8 exhibited inhibitory activity against M. bovis with IC50 values in the range of 4.1–98.5 µM (MIC 13.7–161.0 µM) in the active phase and 4.1–111.1 µM (MIC 13.0–166.4 µM) in the dormant phase.

New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives

Novel tetrazoloquinoline-thiazolidinone conjugates as possible antitubercular agents: synthesis and molecular docking - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Shingate, Bapurao B.; Nawale, Laxman; Sarkar, Dhiman; Khedkar, Vijay M. (Medchemcomm, 2016)
A novel approach for the synthesis of a new 4-thiazolidinone scaffold was developed by a one-pot three-component cyclocondensation of various tetrazolo quinoline aldehydes 1a-f, acid hydrazide 2a-c, and thioglycolic acid 3 in the presence of [DBUH].OAc] as a catalyst in high yields. All the conjugates were screened for their antimycobacterial activity against MTB H37Ra and M. bovis BCG strains, with the MIC values ranging from 0.99-13.55 mu mol mL(-1) and 0.14-20.11 mu mol mL(-1), respectively. The 4-thiazolidinone-incorporated tetrazoloquinoline derivatives 4a, 4d, 4g, 4j, 4m, and 4p were highly potent against MTB H37Ra and M. bovis BCG strains. The most active compounds were also evaluated for their cytotoxicity against MCF-7, A549, and HCT 116 cell lines and were found to be non-cytotoxic. Further, molecular docking studies into the active site of the InhA enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping us to understand the ligand-protein binding interaction and establish a structural basis for the inhibition of mycobacterium tuberculosis. The results suggest that the tetrazoloquinoline-thiazolidinone conjugates 4a, 4d, 4g, 4j, 4m, and 4p are promising antitubercular agents.

New bithiazolyl hydrazones: novel synthesis, characterization and antitubercular evaluation - Bhalerao, Mahendra B.; Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Mane, Ramrao A. (Bioorganic & Medicinal Chemistry Letters, 2017)
New bithiazolyl hydrazones (6a–l) have been first time synthesized by carrying novel one pot cyclocondensation of 5-acyl thiazoles (1a–b), thiosemicarbazide (2) and substituted phenacyl chlorides (4a–f) in freshly prepared ionic liquid, diisopropyl ethyl ammonium acetate (DIPEAc) at room temperature. The newly synthesized compounds have been evaluated for their antitubercular activity and the compounds 3b, 6a, 6b, 6d, 6e, 6f, 6g, and 6l have displayed noticeable antitubercular activity compared to Rifampicin with tolerable cytotoxicity. All these compounds were also screened for their antibacterial activity and found that, compounds 6j and 6k have exhibited a very good antibacterial activity. Molecular docking study has shown better harmony with the evaluation trend shown by these compounds under in vitro antitubercular screening.

Novel benzylidenehydrazide-1,2,3-triazole conjugates as antitubercular agents: synthesis and molecular docking - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar; Nawale, Laxman; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash; Shingate, Bapurao B. (Mini Reviews in Medicinal Chemistry, 2018)
Novel 1,2,3-triazole based benzylidenehydrazide derivatives were synthesized and evaluated for antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra, M. bovis BCG and cytotoxic activity. Most of the derivatives exhibited promising in vitro potency against MTB characterized by lower MIC values. Among all the synthesized derivatives, compound 6a and 6j were the most active against active and dormant MTB H37Ra, respectively. Compound 6d was significantly active against dormant and active M. bovis BCG. The structure activity relationship has been explored on the basis of anti-tubercular activity data. The active compounds were also tested against THP-1, A549 and Panc-1 cell lines and showed no significant cytotoxicity. Further, the synthesized compounds were found to have potential antioxidant with IC50 range = 11.19-56.64 μg/mL. The molecular docking study of synthesized compounds was performed against DprE1 enzyme of MTB to understand the binding interactions. Moreover, synthesized compounds were also analysed for ADME properties and from all the experimental results, the potency of compounds indicate that, this series considered as starting point for the developement of novel and more potent anti-tubercular agents in future.

Novel red fluorescence protein based microplate assay for drug screening against dormant mycobacterium tuberculosis by using paraffin - Yeware, Amar; Sarkar, Dhiman (Tuberculosis, 2018)
The hypoxia model of dormancy is widely used in drug screening programs to identify novel inhibitors against latent Mycobacterium tuberculosis disease. In earlier reported microplate assays, hypoxia was maintained by either sealing the microplate or shifting in an anaerobic chamber to develop dormant phenotype. In these assays, inhibitors were added during inoculation, which mainly represents the active stage inhibitors instead of the dormant ones. Herein, the culture was covered with paraffin to develop hypoxia condition and consequently providing the advantage of adding compounds at any stage during incubation of 96-well plate. The stable expression of the red fluorescent protein in the bacilli under both actively growing as well as dormant conditions also facilitate the reliable estimation of growth and inhibition kinetics of bacilli in medium. Furthermore, S/N ratio and Z' factor of this assay were found to be > 27 and 0.91-0.94 respectively, which confirm the robustness of the protocol. This newly developed drug-screening assay offers an easy, inexpensive, safe and high throughput-screening tool to search novel antitubercular inhibitors against both active and dormant bacilli. The red fluorescent H37Ra strain is a suitable surrogate for the more virulent H37Rv strain, and thus this effort will help in combating latent tuberculosis.

Non nucleoside reverse transcriptase inhibitors, molecular docking studies and antitubercular activity of thiazolidin-4-one derivatives - Chitre, Trupti S.; Patil, Shital M.; Sujalegaonkar, Anagha G.; Asgaonkar, Kalyani D.; Khedkar, Vijay M.; Garud, Dinesh R.; Jha, Prakash C.; Gaikwad, Sharddha Y.; Kulkarni, Smita; Choudhari, Amit; Sarkar, Dhiman (Current Computer-Aided Drug Design, 2019)
Background: Management of Co-existence of Acquired immunodeficiency syndrome and Tuberculosis has become a global challenge due to the emergence of resistant strains and pill burden. Objective: Hence the aim of the present work was to design and evaluate compounds for their dual activity on HIV-1 and Tuberculosis (TB). Methods: A series of seven, novel Thiazolidin-4-one derivatives were synthesized and evaluated for their anti-HIV and anti-tubercular activity along with Molecular docking studies. All the seven compounds displayed promising activity against the replication of HIV-1 in cell-based assays. The four most active compounds were further evaluated against X4 tropic HIV-1(UG)(070) and R5 tropic HIV-1(vB59) primary isolates. The binding affinity of all the designed compounds for HIV-RT and Mycobacterium tuberculosis Enol Reductase (MTB InhA) was gauged by molecular docking studies which revealed crucial thermodynamic interactions governing their binding. Results: The CC50 values for the test compounds were in the range of, 15.08-34.9 mu g/ml, while the IC50 values were in the range of 16.1-27.13(UG(070); X4) and 12.03-23.64 (VB59; R5) mu g/ml. The control drug Nevirapine (NVP) exhibited CC50 value of 77.13 mu g/ml and IC50 value of 0.03 mu g/ml. Amongst all these compounds, compound number 3 showed significant activity with a TI value of 2.167 and 2.678 against the HIV-1 X4 and the R5 tropic virus respectively. In anti-mycobacterial screening, the compounds proved effective in inhibiting the growth of both log phase and starved MTB cultures. Conclusion: Compound 3 has been found to be active against HIV-1 as well as MTB.
Keywords: anti-HIV-1 activity; Antitubercular activity; human immunodeficiency virus-1; Molecular docking; Non nucleoside reverse transcriptase; thiazolidin-4-ones

Novel gene similar to nitrite reductase (NO forming) plays potentially important role in the latency of tuberculosis - Agrawal, Sonia; Gample, Suwarna; Yeware, Amar; Sarkar, Dhiman (Scientific Reports, 2021)
The development of the latent phenotype of Mycobacterium tuberculosis (Mtb) in the human lungs is the major hurdle to eradicate Tuberculosis. We recently reported that exposure to nitrite (10 mM) for six days under in vitro aerobic conditions completely transforms the bacilli into a viable but non-cultivable phenotype. Herein, we show that nitrite (beyond 5 mM) treated Mtb produces nitric oxide (NO) within the cell in a dose-dependent manner. Our search for the conserved sequence of NO synthesizing enzyme in the bacterial system identified MRA2164 and MRA0854 genes, of which the former was found to be significantly up regulated after nitrite exposure. In addition, the purified recombinant MRA2164 protein shows significant nitrite dependent NO synthesizing activity. The knockdown of the MRA2164 gene at mRNA level expression resulted in a significantly reduced NO level compared to the wild type bacilli with a simultaneous return of its replicative capability. Therefore, this study first time reports that nitrite induces dormancy in Mtb cells through induced expression of the MRA2164 gene and productions of NO as a mechanism for maintaining non-replicative stage in Mtb. This observation could help to control the Tuberculosis disease, especially the latent phenotype of the bacilli.